Software Development Superstream Becoming a senior software engineer 2023 - Gee, Trisha; Leandro, Sabrina; Solana, 'Wolé; Helfand, Heidi (O'Reilly Media, Inc., 2023)
As software development grows more complicated and becomes increasingly central to a business's identity, the demand is high for developers who operate at a senior level. Join us to level up your skills and accelerate your journey to senior software engineer. These in-depth sessions cover some of the biggest challenges facing software developers today, teaching you practical methods and best practices to improve coding and software design, better manage data, mentor new engineers, and collaborate with your team. About the Software Development Superstream Series: This series will help you elevate your technical skills, become a better project manager, and build the other professional skills that will allow you to move into senior engineering roles. What you'll learn and how you can apply it Learn how to contribute at a high level, drive big projects, and determine tech strategy Understand what's really important for career development Determine what you should be working on, set your goals, and define your backlog of work This recording of a live event is for you because... You're a developer who wants to find your skills gaps and upskill accordingly to move to the senior or staff level. You want to better understand what work matters the most at every stage of your career and learn how to build the skills you need to support your journey. Recommended follow-up: Read The Staff Engineer's Path (book) Read Software Engineering at Google (book) Listen to The Manager's Path (audiobook) Read Mentoring (book) Take From Developer to Software Architect (live online training course with Nathaniel Schutta) Take Fundamentals of Software Engineering in 3 Weeks (live online training course with Nathaniel Schutta) Take Hands-On Software Design (live online training course with Venkat Subramaniam) Take Introduction to Critical Thinking (live online training course with Connie Missimer) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.
Online resource; title from title details screen (O'Reilly, viewed March 21, 2023)
Keywords: Computer engineering; Vocational guidance; Ordinateurs; Conception et construction; Instructional films; Internet videos; Nonfiction films; Films de formation; Films autres que de fiction; Vidéos sur Internet